2020
DOI: 10.1007/s00520-020-05398-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among Ethiopian cancer patients

Abstract: Purpose Cancer is of increasing prevalence in less-developed countries. However, research on the patients' quality of life (QoL) in these countries is very limited. The aim of this study was to examine QoL of cancer patients in Africa. Method A sample of 256 cancer patients treated in an Ethiopian hospital was examined with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire EORTC QLQ-C30, the Multidimensional Fatigue Inventory, and the Hospital Anxiety and Depression S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 33 publications
1
36
1
Order By: Relevance
“…The needs of patients with non-malignant conditions are also increasingly identi ed [39][40][41]. This research found that patients diagnosed with advanced illnesses in Bhutan have poor levels of functioning and varied levels of symptom severity indicating high support needs, consistent with advanced illnesses in other LMICs [33,[42][43][44][45]. Both cancer and non-cancer patients in Bhutan reported substantial symptom burdens.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The needs of patients with non-malignant conditions are also increasingly identi ed [39][40][41]. This research found that patients diagnosed with advanced illnesses in Bhutan have poor levels of functioning and varied levels of symptom severity indicating high support needs, consistent with advanced illnesses in other LMICs [33,[42][43][44][45]. Both cancer and non-cancer patients in Bhutan reported substantial symptom burdens.…”
Section: Discussionmentioning
confidence: 76%
“…Forty one percent of the Bhutanese patients in this study did not go to school and 13% had just primary education-indicating that 54% of the patients had signi cant problems with literacy. In the Ethiopian study [33] previously discussed, 53% of patients were also illiterate. DeWalt and colleagues in their systematic review on literacy and health outcomes concluded that "low literacy is associated with a range of adverse health outcomes" [60] (p. 1238).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations